Evolusi Informasi : Contoh pada Bagian Personalia - Edy Supriyanto (Universitas Stikubank, 2003)
The meaning of data and informations, most of people sometimes think as same as. But really, it's difference. This passage explain their differences. Also, the passage shows the steps for producing information in three major operations : input, process, and output. Besides this, for many decades, information grew up very fast and very easy. So we know about DSS (Decision Support Systems), EIS (Executive Information Systems, ES (Expert Systems), etc. And then, the writer give an example for information evolution in personnel systems